Effects of Number of Atoms, Shell Thickness, and Temperature on the Structure of Fe Nanoparticles Amorphous by Molecular Dynamics Method - Dung Nguyen Trong; Van Cao Long (Advances in Civil Engineering)
This study aims to study the effect of several structural factors, such as number of atoms (N), shell thickness (d), and temperature (T), on the structure of amorphous iron nanoparticle (amorphous nano-Fe) by using the molecular dynamics (MD) method with Sutton–Chen (SC) dip interaction and free boundary conditions. The structural parameters of amorphous nano-Fe include their size (D), energy (E), radial distribution function (RDF), coordination number (CN), and coordination number density (CNd). The results show that the glass temperature (Tg) and the first peak position (r) of radial distribution function (RDF) have the values of Tg = 900 K and r = 2.55 Å, respectively. Furthermore, the values of parameters D and E are always proportional to N−1/3 and N−1, respectively. Regarding the effect of number of atoms, shell thickness, and the temperature on the structure of amorphous nano-Fe, we found that the increase in atoms number leads to decrease in the RDF height and increase in the coordination number (CN). However, increasing temperature leads to decreasing the shell thickness of amorphous nano-Fe.